A flexible organic resistance memory device for wearable biomedical applications. (31st May 2016) - Cai, Yimao; Tan, Jing; YeFan, Liu; Lin, Min; Huang, Ru
Abstract: Parylene is a Food and Drug Administration (FDA)-approved material which can be safely used within the human body and it is also offers chemically inert and flexible merits. Here, we present a flexible parylene-based organic resistive random access memory (RRAM) device suitable for wearable biomedical application. The proposed device is fabricated through standard lithography and pattern processes at room temperature, exhibiting the feasibility of integration with CMOS circuits. This organic RRAM device offers a high storage window (>10 4 ), superior retention ability and immunity to disturbing. In addition, brilliant mechanical and electrical stabilities of this device are demonstrated when under harsh bending (bending cycle >500, bending radius <10 mm). Finally, the underlying mechanism for resistance switching of this kind of device is discussed, and metallic conducting filament formation and annihilation related to oxidization/redox of Al and Al anions migrating in the parylene layer can be attributed to resistance switching in this device. These advantages reveal the significant potential of parylene-based flexible RRAM devices for wearable biomedical applications.